2021
DOI: 10.1039/d0qi01188f
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced excited spin state trapping in iron(iii) complexes

Abstract: This review discusses the correlation of the local and whole molecular structure of iron(iii) complexes with the magnetic properties including the light-induced excited spin-state trapping (LIESST) effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 75 publications
0
34
0
Order By: Relevance
“…The phenomenon is relatively common for 3d 4 -3d 7 metal centres. 5 While many of the spin crossover complexes that have been studied are octahedral Fe(II) complexes with nitrogen [5][6][7][8][9][10] ligands, other examples include Fe(III) 4,[11][12][13][14] , Co(II) [15][16][17] and Ni(II) 18 . The change in electronic structure, as a result of the spin crossover, can result in changes in properties including molecular structure, colour and magnetism.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The phenomenon is relatively common for 3d 4 -3d 7 metal centres. 5 While many of the spin crossover complexes that have been studied are octahedral Fe(II) complexes with nitrogen [5][6][7][8][9][10] ligands, other examples include Fe(III) 4,[11][12][13][14] , Co(II) [15][16][17] and Ni(II) 18 . The change in electronic structure, as a result of the spin crossover, can result in changes in properties including molecular structure, colour and magnetism.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1930's, the first observation of spin crossover was reported. 1 Spin crossover compounds display a reversible high spin (HS) to low spin (LS) transition at a metal centre, which can be induced by external stimuli such as temperature, pressure 2 or light irradiation 3,4 and can occur in both solution and the solid state. The phenomenon is relatively common for 3d 4 -3d 7 metal centres.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the relatively smaller changes in the average Fe–N/O bond distances between the high-spin (HS) and low-spin (LS) states in SCO Fe­(III) compounds, Δ r HL (= | r HS – r LS |), are thought to prohibit the light-induced excited spin-state trapping (LIESST) effect because a small Δ r HL value (∼0.13 Å for Fe III versus ∼0.20 Å for Fe II ) , promotes fast spin relaxation from the metastable HS state to the LS state of the Fe­(III) ion. So, the LIESST effects in SCO Fe­(III) compounds previously did not attract much attention. But since the discovery of the first LIESST effect in the SCO Fe­(III) compound [Fe­(pap) 2 ]­ClO 4 ·H 2 O, it is suggested that the structural distortion parameters of the Fe­(III) coordination sphere, Σ (the sum of the deviation from 90° of the 12 cis -(N/O–Fe–N/O) angles about the iron atom) and Δ∠ HL,total (the sum of the bond angle differences between the different spin states; this parameter is calculated by using 15 cis and trans (N/O–Fe–N/O) bond angles), instead of the Δ r HL value determine the activation energy for metastable HS-to-LS relaxation, so this discovery has stimulated researchers’ enthusiasm in the study of LIESST effects in SCO Fe­(III) compounds. Strong intermolecular interactions favoring cooperative SCO might contribute to large structural distortion responsible for achieving the LIESST effect but are not necessary. , Reversible LIESST effects in Fe­(II) SCO compounds have been examined systematically since 1986, which have opened up another way for accurate and reversible regulation of the spin states and therefore physical properties of SCO compounds. , Despite these achievements, the design of a bidirectional photocontrolled magnetic switching in the Fe­(III) SCO system remains a daunting challenge. ,, …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Among the versatile stateof-the-art proposals, spin-crossover (SCO)-active first-row transition metal complexes with 3d n (n = 4-7) electronic configuration represent the most promising candidates, which are capable of undergoing a reversibly and controllably switchable characteristic between high spin (HS) and low spin (LS) states in response to external multiple stimuli. [5][6][7][8][9][10][11][12][13] Of particular interest are iron(II) SCO systems featuring an abrupt and stepwise transition with thermal hysteresis (DT 1/2 ), [14][15][16][17][18] a laser pulse-induced spin state switching inside thermal hysteresis loop 19,20 as well as the synergy with functionality, [21][22][23][24][25][26] which have rendered themselves suitable for the realization of molecular electronic and spintronic devices. 22 In contrast to the overwhelming majority of SCO complexes containing classical 3d 4 -3d 7 magnetic centres, equal attention to systems involved with the ''anomalous magnetism'' of d 8 ions is far behind.…”
mentioning
confidence: 99%